A new three-stage gearbox concept for high reduction ratios: Use of a nested-cycloidal architecture to increase the power density. (March 2023) - Maccioni, Lorenzo; Concli, Franco; Blagojevic, Mirko
Abstract: Increasing the Gear Ratio (GR) while decreasing the gearbox dimension is a contradiction that mechanical designers are challenged to solve. The increasing importance of fine-tuning high power density designs has led to the development of innovative solutions involving cycloidal and hypocycloidal gears. However, when the required GR increases and the number of the stages raises, the gearbox architecture plays a key role in minimizing the overall dimensions. In the present paper, an innovative gearbox architecture is presented. The new design combines three cycloidal and hypocycloidal gearing stages to achieve a higher GR with respect to a traditional two-stage cycloidal gearbox with the same overall dimension. This architecture is called Nested since it involves stages with internal and external gears arranged one inside the other. A comparison of the proposed solution with the more compact two-stage cycloidal architecture (Wolfrom) is shown. The GRs as a function of the total number of meshing features are discussed as well as the torques acting on each component. Eventually, a design solution is illustrated. Highlights: A novel gearbox architecture capable of highly compacting three stages is presented. Such architecture involves the third stage nested inside the second one. This enables the design of a 3-stage gearbox with similar dimensions to a 2-stage one. This concept can be implemented either with cycloidal profiles or with involute teeth. Kinematics, torques, and design space are presented, compared, and discussed.